Antibiotic Susceptibility of Lactic Acid Bacteria Isolated From Cow, Goat, Donkey, Buffalo, Sheep, Camel and Human Milk - Yilmaz Nurten; Ala A. Samet; Göncü Serap; Zülkadir Uğur; Barutçu Adnan; Anitaş Özgül (BIO Web of Conferences, 2024)
Breast milk is a very important factor in regulating gastrointestinal function, improving the immune system and preventing acute illnesses (e.g. acute otitis media), especially during breastfeeding. Breast milk allows beneficial bacteria such as bifidobacteria and lactobacillus species to colonise the newborn intestin*e instead of potential enteropathogenic bacteria such as streptococci and escherichia coli. The aim of the study was to compare the antibiotic resistance of Lactic acid bacteria members isolated from different milk samples. Six milk samples were collected from each of seven different milk sources (donkey, goat, cow, buffalo, sheep, camel and human). The MRS and M-17 medium were used with the double layer sandwich method for isolation of LAB members selected from typic colonies, gram-positive, catalase-negative used in the study. The isolated 42 LAB species were determined antibiotic susceptibility with 9 standart antibiotic discs such as tetracycline, penicillin, kanamycin, streptomycin, rifampin, gentamicin, chloramphenicol, teicoplanin, ciprofloxacin by agar disc diffusion assay test. The 18 LAB isolate were resistant to penicillin, 16 isolate to kanamycin, 14 isolate to gentamicin. LAB isolates such as H1, H4, H5 from Human milk and LAB isolate such as D1 from donkey milk was considered as MDR isolates because they were resistant to at least four of the tested drugs. Among the milks, sheep, camel, buffalo and goat milks were found to be more sensitive to antibiotics on average in the group.